Selective photocatalytic CO2 reduction to CH4 over metal-free porous polyimide in the solid–gas mode. Issue 99 (31st October 2022) - Shit, Subhash Chandra; Powar, Niket S.; Kalita, Priyanka; Paul, Ratul; Xu, Shaojun; Jung, Jin-Woo; Cho, Chang-Hee; In, Su-Il; Mondal, John
Abstract : A metal-free donor–acceptor combined conjugated porous polyimide (PeTt–POP ) photocatalyst exhibited visible-light driven photocatalytic CO2 reduction to CH4 in the gas–solid mode. Abstract : Using a catalyst-free one-pot polycondensation approach, a new donor–acceptor (D–A) based porous polyimide (PeTt–POP ) photocatalyst was developed. PeTt–POP produced CH4 (125.63 ppm g −1 in 6 h) from CO2 under visible light irradiation in the gas–solid mode without the use of co-catalysts or sacrificial agents. The progress of the reaction and the corresponding intermediate species involved in the CO2 reduction were identified by operando DRIFTS experiments, from which a plausible reaction mechanism was proposed.